Advances in Solvent Effects on Catalysis, Electrochemistry, and Energy Storage: Mechanisms and Application - Nikmatusyadiah; Zikri , Ahmadi; Purnamasari , Devi; Bisra, Marido (SAINSTEK International Journal on Applied Science, Advanced Technology and Informatics, 2025)
Choosing the appropriate solvent is a pressing challenge in the development of efficient and selective liquid phase catalytic processes because there is still a lack of predictive understanding about the solvent effect. This study develops an attenuated total reflection infrared spectroscopy method to measure the adsorption isotherms on porous materials in solvent and to distinguish the thermodynamic contributions of pore-phase proton transfer from those of van der Waals interactions within zeolite pore walls. While both the pore diameter and the solvent identity have a major impact on the confinement (adsorption) step, the solvent identity has a greater impact on proton transfer. Combining computational and experimental studies, we find that the optimal sequence for pore-phase proton transfer to pyridine is water, acetonitrile, and 1,4-dioxane.